Gene expression and promoter characterisation of stearoyl-ACP desaturase and acyl carrier protein genes from oil palm (Elaeis guineensis jacq.) fruits - Othman, Ashida (2010)
In this study, the expression profiles of the genes encoding two key proteins, stearoyl-ACP desaturase (SAD1) and acyl carrier protein (pACP3) which are involved in plant fatty acid biosynthesis were analysed and their promoter sequences characterized with the aim of obtaining a better understanding of the regulation of storage oil production in oil palm fruits. Real-time PCR was carried out using RNA extracted from different oil palm tissues including mesocarp at 7, 10, 12, 15, 17 and 19 weeks after anthesis (w.a.a.),kernel (12 and 15 w.a.a.), spear and mature leaves as well as abscisic acid and ethylene treated spear leaves. In the mesocarp, SAD1 showed a sharp increase in expression levels between 7 to 12 w.a.a. reaching a peak at 15 w.a.a. followed by small decline at 19 w.a.a.. Meanwhile pACP3 expression levels increased 45-fold between 7 to 10 w.a.a. remained high until 19 w.a.a. The expression levels of pACP3 were slightly higher than SAD1 between 12 – 19 w.a.a. In kernel, SAD1 and pACP3 expression levels were higher at 12 w.a.a. than 15 w.a.a. and pACP3 was expressed at higher levels than SAD1 in both tissues. Both genes were expressed at much lower levels in leaves and SAD1 was shown to be expressed at higher level than pACP3 in spear leaves. For both genes, ABA and ethylene treatments of spear leaves resulted increases in expression levels. For SAD1 and pACP3 promoter isolation, genomic DNA from oil palm spear leaves was isolated and digested with seven different blunt end restriction enzymes: DraI, EcoRV, PvuII, ScaI, StuI, MssI, and SmiI, to produce seven different GenomeWalker libraries. One gene-specific primer and one gene-specific nested primer were designed based on the 5’ –untranslated region (UTR) of both genes and used for genome walking in isolating the to be expressed at higher level than pACP3 in spear leaves. For both genes, ABA and ethylene treatments of spear leaves resulted increases in expression levels. For SAD1 and pACP3 promoter isolation, genomic DNA from oil palm spear leaves was isolated and digested with seven different blunt end restriction enzymes: DraI, EcoRV, PvuII,ScaI, StuI, MssI, and SmiI, to produce seven different GenomeWalker libraries. One gene-specific primer and one gene-specific nested primer were designed based on the 5’–untranslated region (UTR) of both genes and used for genome walking in isolating the promoter sequences. Sequence alignment of the isolated promoters with their respective cDNAs showed 100% sequence identity. The transcription start sites (TSS) of both genes were determined using 5’-rapid amplification of cDNA ends (5’-RACE) strategy. Based on the results, both SAD1 and pACP3 TSS have an adenine base (A) as their transcription initiation sites. Relative to the TSS, the isolated SAD1 and pACP3 promoter sequences were determined to be 1022 bp and 1227 bp in length, respectively. Identification of cis-regulatory elements using Softberry, PLACE and TRANSFAC softwares showed many motifs in common for both promoters. These include proximal regulatory elements (TATA and CAAT boxes), phytohormone responsive [abscisic acid (Athb1, ACGTATERD1 MYB1AT), gibberillic acid (GAmyb), ethylene (ERE)], light responsive (CIACADIANLELHC, Dof1, Dof2, -10PEHVPSBD, EBOXBNNAPA,GATABOX, EALPHALGLHCB2), abiotic factors/wounding responsive (OSE2ROOTNODULE, WBOXATNPR1, WBOXHVISO1, WBOXNTERF3, WRKY71OS), cold or drought responsive (MYCCONSENSUSAT) and endosperm specificity (PBF, DOFCOREEZM, RYREPEATBNNAPA). Using these two genes as models, a better insight on the transcriptional control of fatty-acid biosynthetic genes during period of oil synthesis in oil palm fruits has been achieved in this study. promoter sequences. Sequence alignment of the isolated promoters with their respective cDNAs showed 100% sequence identity. The transcription start sites (TSS) of both genes were determined using 5’-rapid amplification of cDNA ends (5’-RACE) strategy. Based on the results, both SAD1 and pACP3 TSS have an adenine base (A) as theirtranscription initiation sites. Relative to the TSS, the isolated SAD1 and pACP3 promoter sequences were determined to be 1022 bp and 1227 bp in length, respectively. Identification of cis-regulatory elements using Softberry, PLACE and TRANSFAC softwares showed many motifs in common for both promoters. These include proximal regulatory elements (TATA and CAAT boxes), phytohormone responsive [abscisic acid (Athb1, ACGTATERD1 MYB1AT), gibberillic acid (GAmyb), ethylene (ERE)], light responsive (CIACADIANLELHC, Dof1, Dof2, -10PEHVPSBD, EBOXBNNAPA,GATABOX, REALPHALGLHCB2), abiotic actors/wounding responsive (OSE2ROOTNODULE, WBOXATNPR1, WBOXHVISO1, WBOXNTERF3,WRKY71OS), cold or drought responsive (MYCCONSENSUSAT) and endosperm specificity (PBF, DOFCOREEZM, RYREPEATBNNAPA). Using these two genes as models, a better insight on the transcriptional control of fatty-acid biosynthetic genes during period of oil synthesis in oil palm fruits has been achieved in this study.